2009 IEEE International Geoscience and Remote Sensing Symposium 2009
DOI: 10.1109/igarss.2009.5417525
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of precipitation effects in space-borne X- and Ka-band SAR imaging

Abstract: As the operating frequencies of SAR-systems are increasing, the visible distortions due to precipitation in SAR-images are becoming more frequent. This holds especially for the case of convective rain events. The German space-borne satellite TerraSAR-X has delivered a series of measurement examples, which were used to study precipitation effects in SARimages. Based on these valuable data takes and simultaneous weather radar measurements, a quantitative estimation of precipitation effects in SAR-images is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The short wavelength X-band SAR signals are prone to multiple scattering at canopy level hence will not be useful to map the inundated status of densely vegetated or over the forest regions, also the X-band SAR sensors produce cloud shadows due to the attenuation of short wavelength signals. 26,27 The C-band SAR data exhibit encouraging results over the regions where vegetation cover is sparse and used when the availability of high-frequency SAR sensor coverage is limited. 28 With reference to identifying suitable SAR polarization data for the flood area mapping application, it has been observed that the flooded areas would be easier to identify with like-polarized data rather than crosspolarized data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short wavelength X-band SAR signals are prone to multiple scattering at canopy level hence will not be useful to map the inundated status of densely vegetated or over the forest regions, also the X-band SAR sensors produce cloud shadows due to the attenuation of short wavelength signals. 26,27 The C-band SAR data exhibit encouraging results over the regions where vegetation cover is sparse and used when the availability of high-frequency SAR sensor coverage is limited. 28 With reference to identifying suitable SAR polarization data for the flood area mapping application, it has been observed that the flooded areas would be easier to identify with like-polarized data rather than crosspolarized data.…”
Section: Resultsmentioning
confidence: 99%
“…25 With reference to frequency of the SAR signals, the X-band SAR sensors (2.4 to 3.75 cm) produces cloud shadows in the calibrated SAR image due to the attenuation of the short wavelength of the X-band signals. 26,27 During flood-related disasters, the cloud formation over the disaster region is a parallel event. Hence, higher wavelength SAR data are preferred to map the inundated regions.…”
Section: Sar Signal Response Over the Inland Water Bodiesmentioning
confidence: 99%
“…For calculation rain rates which cause apparent attenuation in distinct frequency-band SAR images, a classic model [4] is used. Height of rainfall is assumed as 4 km, when rain rate is considered homogenous in this model.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…However, SAR images might be significantly damaged by the high-intensity rainfall, when radar wave goes through the precipitation media along the propagation path [3][4]. For the analysis of rainfall attenuation effects, the attenuation is conveniently subdivided into two major kinds, i.e., scattering attenuation and absorption loss [5].…”
Section: Introductionmentioning
confidence: 99%
“…To quantify attenuation of radar backscatter induced by rain fall, Urlaby [25] proposed a radiative transfer model for C-band radar. Danklmayer and Chandra [26] present a model to quantify the attenuation for Ka-and X-band SAR. This two-way path attenuation model is given as:…”
Section: Influence Of Rainfall On X-band Sar Data and Its Retrieved Smentioning
confidence: 99%